Impact of Climate Change on the Thermoeconomic Performance of Binary-Cycle Geothermal Power Plants - Paolo Blecich; Igor Wolf; Tomislav Senčić; Igor Bonefačić (Engineering Proceedings)
The thermoeconomic performance of geothermal power plants is influenced by a variety of site-specific factors, major economic variables, and the type of the involved technology. In addition to those, ambient conditions also play a role in geothermal power generation by acting on the cooling towers. This study focuses on the performance analysis of a binary cycle with isobutane for geothermal power generation under the impact of climate change. Long-term temperature variations in ambient air are described by temperature anomalies under two shared socioeconomic pathways (SSP). These are the intermediate SSP2-4.5 scenario and the extreme SSP5-8.5 scenario, over the period from 2021 to 2100. Different climate models from the most recent Climate Model Intercomparison Project (CMIP6) are compared against each other and against the observed temperature data. The predictive power of the CMIP6 climate models is evaluated using the root mean square error (RMSE) and the Kullback–Leibler (KL) criteria. The thermoeconomic performance of the geothermal power plant is expressed in terms of net power output, annual electricity generation (AEG), and levelized cost of electricity (LCOE). The geothermal power plant achieves a net power output of 10 MW and an LCOE of 79.2 USD/MWh for an ambient air temperature of 12 °C. This temperature is the average temperature over the reference period of 1991–2020 in Bjelovar, Croatia (45.8988° N, 16.8423° E). Under the impact of climate change, the same geothermal power plant will have the AEG reduced by between 0.5% and 2.9% in the intermediate (SSP2-4.5) scenario and by between 2.0% and 8.7% in the extreme (SSP5-8.5) scenario. The LCOE will increase between 0.4% and 1.8% in the intermediate scenario and from 1.3% to 5.6% in the extreme scenario.